Type 2 Diabetes, the Epidemic: Trends in Prevalence and Incidence, 2004-2020 - Overbeek JA; Nijpels G; Swart KMA; Blom MT; Elders PJM; Herings RMC (Diabetes, Metabolic Syndrome and Obesity, 2024)
Jetty A Overbeek,1,2 Giel Nijpels,2 Karin MA Swart,1,2 Marieke T Blom,2,3 Petra JM Elders,2,3 Ron MC Herings1,4 1PHARMO Institute for Drug Outcomes Research, Utrecht, Netherlands; 2Amsterdam UMC, Location Vrije Universiteit Amsterdam, Department of General Practice, Amsterdam, Netherlands; 3Amsterdam Public Health, Health Behaviors & Chronic Diseases, Amsterdam, Netherlands; 4Amsterdam UMC location Vrije Universiteit Amsterdam, Department of Epidemiology and Data Science, Amsterdam, NetherlandsCorrespondence: Jetty A Overbeek, Email jetty.overbeek@pharmo.nlAims/Hypothesis: Only a few studies reported the incidence of type 2 diabetes (T2D). Understanding recent trends in diabetes is vital for planning future diabetes care. This study updated national trends in the prevalence and incidence of type 2 diabetes (T2D) in the Netherlands from 2004– 2020.Methods: The DIAbetes, MANagement and Treatment (DIAMANT) cohort was used. A cross-sectional design with yearly measurements for the study period was used. The prevalence was calculated by dividing the total number of people with T2D by the total number of all residents. The incidence was calculated by dividing new cases of T2D by the resident population at risk during the calendar year of interest.Results: Among men, the prevalence of T2D in the Netherlands increased from 2.3% in 2004 to 6.3% in 2020. Women’s prevalence increased from 2.3% in 2004 to 5.3% in 2020. During 2005– 2009, the incidence rate for both men and women was relatively stable Between 2010 and 2020, the incidence rate fell about 1.5 per 1000 in both men and women.Conclusion: From 2004– 2020, the prevalence of T2D in the Netherlands more than doubled, with a decreasing incidence from 2010 onwards.Plain Language Summary: Research in contextWhat is already known about this subject?Many studies have reported the increasing prevalence of type 2 diabetes (T2D). However, only a few studies reported the incidence.In a recent systematic review of all these studies, the incidence fell in over a third of the most high-income populations and increased in a minority of populations. Data from the Netherlands were included, but they date back to 1996.Understanding recent trends in diabetes, the prevalence and incidence are vital for planning future diabetes care.What is the key question?To update national trends in the prevalence and incidence of T2D in the Netherlands for 2004-2020.What are the new findings?During 2004-2020, the prevalence of T2D in the Netherlands more than doubled, with a decreasing incidence from 2010 onwards.How might this impact on clinical practice in the foreseeable future?It demonstrates the effectiveness of preventive strategies, public health education and awareness campaigns contributing to this trend.Keywords: type 2 diabetes, prevalence, incidence, epidemiology